Penerapan Media Promosi Visual Kue Srikaya Kepada Generasi Muda Dalam Upaya Pelestarian Kuliner Tradisional Palembang - Alif Pasya; Hestia Rachmat Nunciata Lubis; Mukhsin Patriansah (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Srikaya cake is one of Palembang's culinary heritage with a sweet taste, followed with a soft texture made of coconut milk, eggs, sugar, and pandan. Despite having a historical value along with a strong culture, Srikaya cake's popularity among the younger generation has actually declined due to a shift in consumption patterns that's heading towards modern culinary trends, such as dessert boxes, bubble tea, and international pastries. In addition to that, the limitations of innovating the marketing, branding, and visual identity has made Srikaya cake less competitive compared to other modern culinary products that are more aggressively promoted on digital platforms. This research solves this problem by designing a visual promotional media that targets the younger generation with the main media in the form of Product Display Panel (PDP), Mini PDP, and packaging variants developed in three tiers consisting of standard, premium, and super premium. The design method applied in this research is Design Thinking, which involves the stages of emphaty towards users, focused problem definition, creative ideas, prototyping, and a testing to receive feedbacks from the target audience. The objectives of the design are to enhance the visual appeal and the perceived value of Srikaya cake, building the brand identity that is relevant to the young generation, and also to expand the promotional reach through both offline and online channels. The expected results are to increase the buying interest, better aesthetic acceptance, and to contribute in preserving the Palembang's traditional culinary heritage through marketing solutions that are adaptive towards the modern market dynamics